2019
DOI: 10.2174/1574885514666181217130259
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Freeze-dried Liposomes Loaded with Amphotericin B

Abstract: Background: Amphotericin B (AmB) is a drug of choice in the therapy of systemic fungal infection because of its board-spectrum antifungal activity. However, its conventional formulation has many side effects such as acute and chronic nephrotoxicity. Liposomes have been developed to reduce the drug’s toxicity. However, they had to meet strict stability criteria. In general, liposomes can be freeze-dried to inhibit liposomes infusion, phospholipids degradation during storage. Liposomal size usually increases aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…It has been reported that the liposomes containing drug molecules can be lyophilized and reconstituted with significant drug retention, which is measured as the percent of the encapsulated drug and without a significant change in the mean vesicle size. Cryoprotectants are needed during lyophilization, and sugars, such as sucrose, lactose, and trehalose, are used to protect the liposomes during the freezing stage of the lyophilization cycle [39,40]. Lyophilization with 9% lactose as a cryoprotectant provided physical stability to the liposomes as well as high protection against liposomal drug leakage.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the liposomes containing drug molecules can be lyophilized and reconstituted with significant drug retention, which is measured as the percent of the encapsulated drug and without a significant change in the mean vesicle size. Cryoprotectants are needed during lyophilization, and sugars, such as sucrose, lactose, and trehalose, are used to protect the liposomes during the freezing stage of the lyophilization cycle [39,40]. Lyophilization with 9% lactose as a cryoprotectant provided physical stability to the liposomes as well as high protection against liposomal drug leakage.…”
Section: Discussionmentioning
confidence: 99%
“…This method involves dissolving of lipid and drug in tert-butyl alcohol at 45 0 C, and lyo-protectant dissolves in water at 45 0 C. Both of the obtained solutions are mixed to form third identical monophasic solution, followed by filtration, and freeze drying of solution is performed to produce proliposomes. Freeze drying involves 2 steps: in first, the sample is frozen at − 40ºC and then dried at room temperature which upon hydration eventually forms liposomes with mean dimension of 100-300 nm [76]. Advantages…”
Section: Freeze Drying Methodsmentioning
confidence: 99%